Development of Nationwide Vs30 Map and Calibrated Conversion Table for Indonesia using Automated Topographical Classification - Masyhur Irsyam; Muhammad Asrurifak; Reguel Mikhail; In In Wahdiny; Siska Rustiani; Munirwansyah Munirwansyah (Journal of Engineering and Technological Sciences, 2017)
A nationwide Vs30 map for Indonesia was developed based on automated topographic classification from 90-m grid digital elevation data and their correlation with Vs30. Automated topographic classification has been proposed by Iwahashi and Pike (2007) and a procedure to convert topographic class into Vs30 maps has been developed by Imamura and Furuta (2015) based on Vs data from J-SHIS (Japan Seismic Hazard Information System). In order to be suitable for Indonesia, calibration work according to Imamura and Furuta's procedure should be conducted since the geotechnical conditions in Japan may not be the same as in Indonesia. This paper presents adjustment of the Vs30 correlation by Imamura and Furuta to convert topographic class into Vs30 and construct a Vs30 map of Indonesia. This correlation was calibrated by using Vs data from BMKG (Indonesian Agency for Meteorological, Climatological, and Geophysics) as well as standard penetration test logs that were collected by the authors. Utilization of local field measurement data will certainly enhance the reliability of the Vs30 map. The developed nationwide Vs30 map will be very useful for disaster mitigation programs and for preliminary design of earthquake resistant buildings and infrastructure in Indonesia.